2011
DOI: 10.1186/1471-2407-11-412
|View full text |Cite
|
Sign up to set email alerts
|

A phenanthrene derived PARP inhibitor is an extra-centrosomes de-clustering agent exclusively eradicating human cancer cells

Abstract: BackgroundCells of most human cancers have supernumerary centrosomes. To enable an accurate chromosome segregation and cell division, these cells developed a yet unresolved molecular mechanism, clustering their extra centrosomes at two poles, thereby mimicking mitosis in normal cells. Failure of this bipolar centrosome clustering causes multipolar spindle structures and aberrant chromosomes segregation that prevent normal cell division and lead to 'mitotic catastrophe cell death'.MethodsWe used cell biology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 43 publications
(71 reference statements)
10
72
0
Order By: Relevance
“…It has been demonstrated that PJ34 was able to prevent the clustering of extra centrosomes in mitosis and exclusively eradicate human cancer cells with supernumerary centrosomes without impairing normal proliferating cells. 11 In the present study, we demonstrated that KIFC1 is upregulated in breast cancer tissues and breast cancer cell lines, and that KIFC1 silencing in breast cancer cells significantly reduced cell viability. Furthermore, we found that PJ34 acts as a small molecule KIFC1 inhibitor by suppressing KIFC1 expression in breast cancer cells.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been demonstrated that PJ34 was able to prevent the clustering of extra centrosomes in mitosis and exclusively eradicate human cancer cells with supernumerary centrosomes without impairing normal proliferating cells. 11 In the present study, we demonstrated that KIFC1 is upregulated in breast cancer tissues and breast cancer cell lines, and that KIFC1 silencing in breast cancer cells significantly reduced cell viability. Furthermore, we found that PJ34 acts as a small molecule KIFC1 inhibitor by suppressing KIFC1 expression in breast cancer cells.…”
Section: Introductionmentioning
confidence: 83%
“…12 Recently, it has been found that PJ34 is a centrosome declustering agent exclusively eradicating human cancer cells. 11 However the molecular mechanism underlying PJ34-induced centrosome declustering was unclear. Interestingly, we found that PJ34 at 7-56 mM was able to markedly suppress KIFC1 expression in breast cancer MDA-MB-231, HS578T and BT549 cells (Fig.…”
Section: Small Molecule Pj34 Suppresses Kifc1 Expression In Breast Camentioning
confidence: 99%
“…The recent development of inhibitors that compromise centrosome clustering could be the beginning of the validation of this idea in vivo. Several inhibitors have been developed that induce multipolar mitosis preferentially in cancer cells, such as a phenanthrene-derived PARP inhibitor, GF-15, a derivative of griseofulvin and taxol [140][141][142]. There is interest in the clinical use of these compounds, such as for example GF-15 which decreases tumour growth in xenograft mouse models [141].…”
Section: Targeting Cells With Extra Centrosomes For Cancer Therapymentioning
confidence: 99%
“…Treatment of tumors exhibiting centrosome amplification with the phenanthrene-derived PARP-1 inhibitor, PJ-34, results in clustering inhibition, spindle multipolarity, and death by mitotic catastrophe. 134 By contrast, treatment of normal proliferating cells with high drug concentration (i.e., 2-3 times greater than necessary for complete PARP-1 inhibition) for several days has no discernible effect on spindle morphology, centrosome integrity, mitosis, or cell viability. PARP-1 is involved in detection and base-excision repair of DNA strand breaks, initiation of the DNA damage checkpoint, and apoptosis, 135 activities not plainly related to clustering.…”
Section: Disperse and Destroy: Induction Of Spindle Multipolarity As mentioning
confidence: 99%
“…Some phenanthrene-derived poly-ADP-ribose polymerase (PARP) inhibitors also exhibit cancer cell-specific declustering. 134 PARP-1 expression is upregulated in various human cancers 135 but downregulated in others, 136 suggesting a complex role for this protein in tumorigenesis. Treatment of tumors exhibiting centrosome amplification with the phenanthrene-derived PARP-1 inhibitor, PJ-34, results in clustering inhibition, spindle multipolarity, and death by mitotic catastrophe.…”
Section: Disperse and Destroy: Induction Of Spindle Multipolarity As mentioning
confidence: 99%